2016
DOI: 10.14746/ssllt.2016.6.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Observing the interactive qualities of L2 instructional practices in ESL and FSL classrooms

Abstract: Discourse features that promote the generation of interactionally modified input and output, such as negotiation for meaning, have been shown to significantly enhance second language acquisition. Research has also identified several characteristics of instructional practices that render them more or less propitious to the generation of these discourse features. While various classroom observation studies have successfully measured the communicative orientation of classroom environments, most of the indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This has limited students’ development of oral skills by creating a closed discourse where teacher talk predominates (Soto-Hinman, 2011; Walqui, & Van Lier, 2010). Whereas it seems essential to transforms classrooms into dialogic spaces for students to develop oral skills as essential for their education, research has revealed that English as Second Language and Foreign Second Language classrooms are not very interactive, since 70% of their practices are teacher-centered or devoted to individual students (Zuniga & Simard, 2016). So that, dialogic contexts are more necessary than ever to change this unidirectional pattern by transforming monologic classrooms to foster students’ participation in the creation of their own knowledge (García-Carrión et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This has limited students’ development of oral skills by creating a closed discourse where teacher talk predominates (Soto-Hinman, 2011; Walqui, & Van Lier, 2010). Whereas it seems essential to transforms classrooms into dialogic spaces for students to develop oral skills as essential for their education, research has revealed that English as Second Language and Foreign Second Language classrooms are not very interactive, since 70% of their practices are teacher-centered or devoted to individual students (Zuniga & Simard, 2016). So that, dialogic contexts are more necessary than ever to change this unidirectional pattern by transforming monologic classrooms to foster students’ participation in the creation of their own knowledge (García-Carrión et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, oral interaction frequently goes underdeveloped in language classrooms. A recent study by Zuniga and Simard (2016), for example, reported that out of 64 hours of classroom observation, Quebec high school language teachers spent 8% of the time developing these interactive skills.…”
Section: Introductionmentioning
confidence: 99%